Instructional strategies for different learning styles: a study - V Prasanthi, B. (SPC Journal of Education, 2019)
Learning is a continuous process for two classes of people (for both teacher & student). We all learns something new every day. It is gaining knowledge by studying; being taught & experiencing, whereas teaching is defined as just a more formal approach to deliver lessons with learning as end result. Teaching & learning are permitted not only within the dimensions, but it should happen beyond that. A learning style can best be explained as the most unique way in which a student prefers to learn new concepts. Students learn quicker and more effectively when teaching style is matched to their individual preferred styles. This paper explains about existing learning styles and also suggests few teaching methodologies that are to be adopted for different learning styles, which creates inter-est in students that leads to outstanding performance in academics.Â Â
Keywords: Learning Styles; Teaching Methodologies; Individual & Collaborative Learning.